Security, corruption, and development: A global view from Compliance perspective. Spanish point of view - Ballesteros Sánchez, Julio (2019)
This paper has as aim to link corporate crimes to corrupt behaviours and to the depreciation of criminal legal assets, human rights and national security. Provided that the enterprise management is responsible, diligent, ethical, based on compliance, enterprises will obtain the security understood as a broad concept. Notwithstanding, enterprises that have a bad governance, an unethical behaviour and a lack of diligence, may become a threat to national security and economic development of States. As a consequence, criminal compliance is related to the concepts of security and human rights in a competitive environment as well as in a world where the welfare state is shrinking.